Coaching positive youth development in Brazil: Recommendations for coach education programs - Gaion, P.; Milistetd, M.; Santos, F.; Contreira, A.; Arantes, L.; Caruzzo, N. (International Sport Coaching Journal, 2020)
Coaching positive youth development (PYD) represents a challenge for many participation and high-performance coaches across the globe, including in Brazil. Coach education has been acknowledged as a formal learning context that may help prepare coaches to effectively foster PYD outcomes and provide high-quality developmental experiences for athletes across different sport contexts. Therefore, the purpose of this paper is to describe the key concepts and existing guidelines for coaching and coach education in Brazil, and provide context-specific recommendations for coach education to include PYD materials. Coaching in Brazil includes a long preparation period that includes diversified opportunities for coach learning. However, there are some discrepancies between the objectives and outcomes prioritized by governing bodies and sport organizations and how learning contexts are framed. In other words, although PYD is considered to be a necessary endeavor, it is not explicitly included in any coach education program. Moving forward, we provide several recommendations, through a bottom-up approach, in order to embed PYD within the Brazilian sport system.